The Involvement Of Indonesian Civil Society Organizations In The Policy-Making Process Of Migrant Workers Protection In ASEAN - Septiyana, Iyan (Journal of Indonesian Social Sciences and Humanities, 2019)
More than 20 millions of ASEAN citizens work overseas as migrant workers. The contribution of migrant workers to economic development for both the destination and the origin countries are respectable. However, for some decades the policy of migrant worker protection was absent since none of ASEAN member states discusses the issue in the regional level. In fact, from the beginning of the migration process, the migrant workers often become victims of human rights violation and workers’ rights violation for instance physical abuse, exploitation, harassment, and discrimination. In 2007 and 2017 ASEAN eventually agreed on migrant workers protection policies. While ASEAN is well-known as a state-centric regional organization, the policy-making process has involved some CSOs. The limited participation space in ASEAN does not hinder the CSOs to bring up the issues in the regional public sphere and to involve in the policy-making process by influencing ASEAN member states through three available spaces for non-state actors. This paper focuses on the involvement of Indonesian CSOs as in the policy-making process on migrant worker protection at the regional level.